2017
DOI: 10.1016/j.ijpe.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The unique chinese innovation pathways: Lessons from chinese small and mediuem sized manufacturing firms

Abstract: Many researchers equate the development of Chinese product innovation capabilities to Japanese and South Korean's development paths, that is, from imitation to innovation. Nonetheless, today many Chinese products have competed successfully in the global markets in terms of speed, cost, quality, and innovativeness. China's product innovation performance has gained the world's recognition. The performance of some industrial areas have also outperformed Japan and South Korea. This paper aims to understand and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…3) Прямые контакты с клиентами помогают совершенствованию продукции и НИС. Исследователи выявили, что в отличие от японских и корейских, китайские малые предприятия совершенствуют продукцию, главным образом, опираясь на отзывы пользователей, а не на результаты НИОКР (Chung, Tan 2017). 4) Появляется возможность заниматься послепродажным сервисным обслуживанием и обновлять программное обеспечение, необходимое для современной продукции Интернета вещей.…”
Section: Mgimo Review Of International Relations • 14(1) • 2021unclassified
“…3) Прямые контакты с клиентами помогают совершенствованию продукции и НИС. Исследователи выявили, что в отличие от японских и корейских, китайские малые предприятия совершенствуют продукцию, главным образом, опираясь на отзывы пользователей, а не на результаты НИОКР (Chung, Tan 2017). 4) Появляется возможность заниматься послепродажным сервисным обслуживанием и обновлять программное обеспечение, необходимое для современной продукции Интернета вещей.…”
Section: Mgimo Review Of International Relations • 14(1) • 2021unclassified
“…In opposition, most of the large and high-tech companies have product development initiatives on their own. One of the reasons for this movement is the cooperation with large Chinese universities as well as greater interaction with Chinese and international clients (Chung & Tan, 2017). Therefore, for the same product line, it seems to be strategic for Company I to balance the purchasing portfolio with companies of different sizes to maintain its competitiveness and absorb product innovations.…”
Section: New Product Developmentmentioning
confidence: 99%
“…Prior studies have enunciated on the innovative capabilities of SMEs (Newman et al, 2015;Chung and Tan, 2017;Gentile-Lüdecke et al, 2019;Mei et al, 2019;Xiang et al, 2019), but few studies have revealed the effect of corporate governance on SME performance (Hsu et al, 2013;Shapiro et al, 2015;Ge et al, 2019;Bauweraerts, 2020). Despite this enormous body of research, the cognition of the CEO has been little explored, though this can boost the firm's growth and maintain sustainable corporate growth.…”
Section: Theoretical Framework and Formulation Of Hypothesesmentioning
confidence: 99%